Orders of Gauss Periods in Finite Fields. - Von zur Gathen, Joachim (Applicable algebra in engineering, communication and computing.)
It is shown that Gauss periods of a special type give an explicit polynomial-time computation of elements of exponentially large multiplicative order in some finite fields. This can be considered as a step towards solving the celebrated problem of finding primitive roots in finite fields in polynomial time.